Diagnostic delay for superficial and deep endometriosis in the United Kingdom. (2nd January 2020) - Ghai, Vishalli; Jan, Haider; Shakir, Fevzi; Haines, Pat; Kent, Andrew
Abstract: A Cross-sectional study was undertaken at a specialist centre in the United Kingdom investigating duration and causes of delay in the diagnosis of endometriosis. One hundred and one women completed a self-reported questionnaire containing 20 items about their psychosocial, symptoms and experiences. The statistical analysis included a Mann-Whitney U test. A p value of .05 was considered statistically significant. The Spearman's rank correlation was also calculated. Overall, there was a median delay of 8 years (Q1–Q3: 3–14) from the onset of symptoms to a diagnosis of endometriosis. Factors such as menstrual cramps in adolescence, presence of rectovaginal endometriosis, normalisation of pain and the attitudes of health professionals contributed to a delayed diagnosis ( p values<.05). There was a negative correlation indicating the earlier the onset of symptoms, the greater the delay to diagnosis (Spearman's Rank Correlation Coefficient –0.63, p <.01). The results of this study highlight a considerable diagnostic delay associated with endometriosis and the need for clinician education and public awareness. Impact statement: What is already known on this subject? The diagnostic delay of 7–9 years with endometriosis has been reported globally. In an effort to standardise surgical treatment, improve outcomes, and shorten delays specialist endometriosis centres were introduced in 2011. There has been no recent quality improvement assessment since the establishment of such centres. What do the results of this study add? This is the most recent evaluation in the United Kingdom since the introduction of specialist endometriosis centres. There is a considerable diagnostic delay associated endometriosis in the United Kingdom with a median of 8 years. The delays seem not to have improved over the last two decades. We have identified medical and psychosocial factors that may contribute to such delays. These include factors such as menstrual cramps in adolescence, presence of rectovaginal endometriosis, normalisation of pain and attitudes of health professionals contribute to a delayed diagnosis. What are the implications of these findings for clinical practice and/or further research? The results of this study, highlight the need for clinician education and public awareness to decrease the long term-morbidity and complications that result from untreated endometriosis.